The Mitochondrial Translocator Protein and the Emerging Link Between Oxidative Stress and Arrhythmias in the Diabetic Heart - Ilkan, Zeki; Akar, Fadi G. (Frontiers in Physiology, 2018)
The mitochondrial translocator protein (TSPO) is a key outer mitochondrial membrane protein that regulates the activity of energy-dissipating mitochondrial channels in response to oxidative stress. In this article, we provide an overview of the role of TSPO in the systematic amplification of reactive oxygen species (ROS) through an autocatalytic process known as ROS-induced ROS-release (RIRR). We describe how this TSPO-driven process destabilizes the mitochondrial membrane potential leading to electrical instability at the cellular and whole heart levels. Finally, we provide our perspective on the role of TSPO in the pathophysiology of diabetes, in general and diabetes-related arrhythmias, in particular.